(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate if an educational intervention can reduce the waste of food and indirect expenses in a commercial restaurant, analyzing before and after the educational action. The work was carried out in three moments: Diagnosis, Intervention and Evaluation. At the diagnosis stage, it was observed that 72% of the proteins received in the restaurant had the percentage of melting above the proposed one. Of the total of the leaflets used in the restaurant 50% had the correction factor above the established, and in relation to the verified vegetables, 75%. Regarding indirect costs, habits such as open faucets, lamps and connected equipment, among others, were observed. After the training and corrective actions only 33% of the proteins had the melting index out of acceptable. Regarding the vegetables, mainly the Swiss chard, lettuce and purple lettuce will decrease the correction factor decreased by 19.12%, 19.2% and 18.83 respectively and the vegetables only verified 15.8% did not decrease the correction factors. With regard to energy, water and gas expenses, there was a systematization of the on / off procedures. Although the intervention was short, spending was considerably reduced, resulting in a savings of 17.5%.